Reduction in Energy Consumption by Mitigation of Cultivation Resistance Due to the New Fallow Harrow Concept - Volodymyr Bulgakov; Volodymyr Nadykto; Olga Orynycz; Simone Pascuzzi (Energies, 2022)
One of the best precursors for winter wheat is fallow. Its application aims to solve two important tasks: preserving and accumulating soil moisture and weed control. The authors of this paper have designed a new modular harrow for fallow tillage, which can work stably at a depth of 5–6 cm tillage while maintaining and even accumulating soil moisture. This article describes a method designed by the authors for a reasonable selection of the design parameters concerning the working devices mounted inside the new harrow, such as their length and working width, as well as the angles of vertical inclination (<semantics>ε</semantics>) and horizontal deviation (<semantics>γ</semantics>) of blades, depending on the accepted depth of the upper soil layer loosening. To reduce the soil tillage resistance of the harrowing unit resulting in a reduction in the tractor fuel consumption, the value of the inclination angle (ε) of its vertical blade should be chosen so that the corresponding change in the value of the deflection angle of the horizontal blade (γ) complies with the constrain of the product of tangents of these angles. Moreover, preference should be given to choosing the value of the angle ε with the subsequent determination of the angle γ value. It is demonstrated that proper use of the new type of harrow assures fuel savings and decreases carbon dioxide emissions even if fossil fuel alone is used. Additional reduction of CO2 emission can be achieved when biofuels are used as a replacement for fossil ones.